1994
DOI: 10.1121/1.410314
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile adaptation enhances frequency discrimination

Abstract: Human vibrotactile frequency discrimination (with respect to a 25-Hz standard stimulus, 20 dB above unadapted detection threshold) was measured on the thenar eminence and index fingerpad, using two-interval forced-choice tracking. Measurements were made in the unadapted state and following exposure to 25-Hz adapting stimuli of various amplitudes. The standard and all comparison stimuli were equated for perceived intensity, on the basis of matching experiments that were carried out separately under each adaptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 0 publications
7
26
0
Order By: Relevance
“…Therefore, a common mechanism would unlikely account for both vibrotactile masking and presentation-order effects. Similarly, in vibrotactile adaptation, sustained stimulation over seconds or minutes at a given frequency results in increased detection thresholds (Craig, 1972(Craig, , 1974Gescheider et aI., 1969;Goble & Hollins, 1993;Hahn, 1966Hahn, , 1968Hollins, Goble, Whitsel, & Tommerdahl, 1990) and lowered amplitude and frequency discrimination thresholds for recovery periods of roughly comparable duration (Goble & Hollins, 1993, 1994. However, adaptation seems an unlikely mechanism for presentation-order effects in the present study with I-sec stimulus durations, relatively long interstimulus intervals, and randomly ordered frequencies.…”
Section: Presentation-order Effectssupporting
confidence: 54%
“…Therefore, a common mechanism would unlikely account for both vibrotactile masking and presentation-order effects. Similarly, in vibrotactile adaptation, sustained stimulation over seconds or minutes at a given frequency results in increased detection thresholds (Craig, 1972(Craig, , 1974Gescheider et aI., 1969;Goble & Hollins, 1993;Hahn, 1966Hahn, , 1968Hollins, Goble, Whitsel, & Tommerdahl, 1990) and lowered amplitude and frequency discrimination thresholds for recovery periods of roughly comparable duration (Goble & Hollins, 1993, 1994. However, adaptation seems an unlikely mechanism for presentation-order effects in the present study with I-sec stimulus durations, relatively long interstimulus intervals, and randomly ordered frequencies.…”
Section: Presentation-order Effectssupporting
confidence: 54%
“…Some studies (Goble and Hollins, 1994) have used frequency-amplitude matching to remove amplitude as a potential driver of frequency discrimination performance (also; Goble and Hollins, 1994). The aim of this study was to develop a short battery of tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Although appreciation of the neural mechanisms remains incomplete, it has become apparent that the perceptual effects of vibrotactile adaptation are not, as early workers believed (Verrillo et al, 1969), attributable solely to peripheral receptor ''fatigue''/desensitization. The clearest examples of this have been provided by Goble and Hollins (1994) and Tommerdahl et al (2005c) who showed that adaptation to a vibrotactile stimulus results in significant improvement of the capacity of subjects to discriminate between vibrotactile stimuli that differ only in frequency when the frequencies of the adapting and standard stimuli are similar, and as indicated in preceding paragraphs Tommerdahl et al (2005c) showed that when the frequencies of the adapting and standard stimuli are very different, human vibrotactile discriminative capacity is degraded following adaptation. These different (opposite) effects of adaptation on human vibrotactile discriminative performance are notable because optical imaging and neurophysiological recording studies in cats and monkeys have reported that the region of contralateral cerebral cortex (SI) widely believed to be essential for normal frequency discriminative performance is influenced in different (essentially opposite) ways by a prolonged exposure to low-vs. high-frequency vibrotactile stimulation.…”
Section: Extended Exposure To Stimulationmentioning
confidence: 93%
“…It should also be considered that the prolonged exposure of the skin to continuous vibrotactile stimulation (''vibrotactile adaptation'') at either 25 Hz or 200 Hz is accompanied by a differential modification of human frequency discriminative capacity. More specifically, whereas a 15 s pre-exposure of a skin site to 25 Hz or 200 Hz adaptation was found to improve human frequency discriminative capacity at frequencies identical or similar to that of the adapting stimulus (Goble and Hollins, 1994), substantial impairment of frequency discrimination occurred at frequencies very different (i.e., at frequencies that evoked a qualitatively distinct sensory experience) than the frequency of the adapting stimulus (Tommerdahl et al, 2005c).…”
Section: Convergence Of Vibrotactile Inputs Across ''Channels''mentioning
confidence: 98%